Reconstruction of rockfall activity through dendrogeomorphology and a scar-counting approach - Žabota, Barbara (Acta silvae et ligni, 2020)
Trees represent an important archive that can be used to reconstruct the spatial and temporal patterns of rockfall events. Rockfall impacts can be recorded in the form of anomalies in tree rings and impact scars on the tree stem. In this paper we demonstrate the use of an approach based on counting scars for reconstructing the frequency and spatial pattern of past rockfalls. The approach was applied by counting the visible scars on the stem surface of 52 European beech trees (Fagus sylvatica L.) in the area of the Trenta Valley, Slovenia. The average number of impacts per trees was 7, and the impacts were mostly classified as old, indicating reduced rockfall activity in recent years. The average recurrence interval was 31.8 years, which was reduced by 1.2 years by the application of the conditional impact probability. The spatial pattern of rockfall impacts shows that rockfall activity is higher in the middle part of the studied slope.
Keywords: dendrogeomorfologija; dendrogeomorphology; drevesne branike; naravne nevarnosti; natural hazards; poškodbe debla; povratna doba; recurrence interval; rockfall; skalni podori; stem scars; tree rings